The AEPEX mission: Imaging energetic particle precipitation in the atmosphere through its bremsstrahlung X-ray signatures. Issue 1 (1st July 2020) - Marshall, Robert A.; Xu, Wei; Woods, Thomas; Cully, Christopher; Jaynes, Allison; Randall, Cora; Baker, Daniel; McCarthy, Michael; Spence, Harlan E.; Berland, Grant; Wold, Alexandra; Davis, Elliott
Abstract: The Atmospheric Effects of Precipitation through Energetic X-rays (AEPEX) mission is a 6U CubeSat that will monitor energetic electron precipitation from the radiation belts into the upper atmosphere. The primary instrument will image energetic (50–300 keV) X-rays produced in the atmosphere by bremsstrahlung, providing a near-direct signature of electron precipitation. An energetic electron detector will measure the precipitating electron spectrum, while the X-ray observations will be used to determine the absolute flux. X-ray images will be produced with 10-s time resolution and 50–100 km spatial resolution. The 6U spacecraft uses flight heritage spacecraft bus subsystems, including the attitude determination and control, electrical power, and command & data handling systems. AEPEX is designed to be operated from low-Earth orbit at ~ 500 km altitude with a high inclination in order to cover the outer radiation belt. AEPEX will be the first spacecraft mission to measure X-rays in the 50–300 keV energy range emitted by Earth's atmosphere in response to radiation belt precipitation, and the first to image that precipitation from above.